Analisis Kesulitan Siswa dalam Mempelajari Materi Bangun Ruang Sisi Datar pada Siswa Kelas VIII SMP Negeri 2 Ponelo Kepulauan - Monalisa Noe; Perry Zakaria; Auli Irfah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyse the difficulties experienced by students in learning about flat-sided three-dimensional shapes. The research method employed is descriptive with a qualitative approach. The data collected in this study were obtained from students’ difficulty tests and interview results. The research subjects were Year 8 pupils at SMP Negeri 2 Ponelo Kepulauan in the 2024/2025 academic year. The interviews were conducted by selecting three questions related to difficulties in learning mathematics, with one student chosen as a respondent to be interviewed on 26 August 2025. The indicators used to assess students’ learning difficulties were: facts, principles, concepts, and operations. The research results indicate that students with the lowest marks demonstrated limitations in mastering all the indicators measured when solving mathematics problems on the topic of flat-sided three-dimensional shapes. During the interview, students with the lowest marks experienced difficulties despite the use of effective teaching methods. This was because they paid insufficient attention to what the teacher was explaining.